Vprašanje feministične teorije v šolskem polju - Vendramin, Valerija (Šolsko polje, 2007)
The article introduces the following questions: how to consider the influence of feminist theory in the school field? Which are those components where the reflection seems to be most urgent and most productive? Which aspects of education can feminist theory bring to the forefront and which are the difficulties, contradictions or even deficiencies of the so called feminist pedagogy? The author further deals with some concepts that are fundamental to education (e.g. experience, official knowledge) and tries to evaluate them critically. The key potential of such reflection is to be seen in the destabilization or, at least, an attempt at destabilization of meanings (this is one of the most important aspects of feminist theory), in the struggle for public knowledge, for what is going to count as rational descriptions of the world.
Keywords: feministična teorija; feminizem; izkustvo; izobraževanje; kurikulum; objektivnost